PUBLIC COMMUNICATION OF COVID-19 VACCINATION OF TANAH DATAR GOVERNMENT THROUGH DIGITAL MEDIA - Okditazeini, Vannyora; Marzal, Novrizon; Jamilus, Jamilus; Sari, Meily Puspita; Kirana, Nilam Putri (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2024)
Given the importance of the presence of the COVID-19 Vaccine/Vaccination, countries in the world, including Indonesia, make the provision of the COVID-19 Vaccine/Vaccination a priority in overcoming the COVID-19 Pandemic. Data on vaccination achievement in West Sumatra as of January 22, 2022 shows that Tanah Datar Regency ranks the third lowest for vaccine achievement in the West Sumatra region. This figure is certainly worrying because it could threaten the smooth running of the government's COVID-19 vaccination program to tackle the COVID-19 pandemic in West Sumatra province. For this reason, it is necessary to see how public communication is carried out by the land district government regarding the covid-19 vaccination program. This study uses content analysis to display several posts from the Tanah Datar district government, both from official channels and on their social media. The results of the study show that at least in delivering information related to the Covid-19 vaccination program, the Tanah Datar district government uses 3 (three) approaches, including; (1) Report transparency; (2) Socialization and invitations; and (3) Sanctions.